THE COLORFUL WORLD OF PUBLIC HOUSES. OWNERSHIP, CLIENTELE AND LEISURE TIME ACTIVITIES IN 18th CENTURY TIMIŞOARA - Hirsch, Sandra (Journal of Education Culture and Society, 2020)
Timişoara became a rightful provincial capital of an Austrian domain during the 18th Century. In this period an important number of citizens chose to build and run inns or taverns as landlords or just as leaseholders. The archive documents from Timişoara put together the puzzle pieces that recreate the stories of old public houses; they also contain information regarding all sorts of activities connected to the microcosm of taverns. Therefore the aim of this paper is to discover who the owners of inns were, why did they choose this trade and what was their place in Timişoara’s society. The clientele, less highlighted in documents, also plays a role through the choices of spending their leisure time in such places, through activities they fancied: music, gambling, billiards, bowling and the products they ordered for consumption. All these aspects enable us to shed light one of the most vivid parts of 18th century urban life.